The effects of health threatening messages on non-milk drinkers defensiveness or acceptance resulting from self-affirmation - Caram, Kathrina Marie A.
Sixty females working in identified government agencies in Iloilo City participated in the study investigating whether non-molk drinkers accept or become defensive towards a health threatening message after self-affirmation was given. There were four conditions applied during the experiment and these were the following: milk drinkers with self-affirmation, milk drinkers without self-affirmation, non-milk drinkers with self-affirmation, and non-milk drinkers without self-affirmation. With an alpha level ( )=..05, f critical=4.75 and f computed=19.34, the finding or results showed that there is a significant difference in the population mean of acceptance between the self-affirmation group and non self-affirmation group. Self affirmation theory (Sherman et al., 2000) states that thoughts and actions are motivated by a desire to maintain a self-image as moral, adaptive, and capable.